Financial information transfer in municipal government: An exploratory examination of government financial officers' communication. Issue 2 (3rd June 2019) - Jones, Janet R.; Holmes, Amy Foshee; Fischer, Mary; Cole, Brooklyn
Abstract : Purpose: The purpose of this paper is to investigate how trust, honesty and transparency impact the willingness and timeliness of communicating financial information between Government Finance Officers (GFOs) and members of the municipal boards they serve. Design/methodology/approach: Survey data was collected from professionals who work with municipalities to ensure government resources are properly managed. Nonparametric local-linear regression was used to analyze the data. Findings: Evidence suggests that trust in the board, GFO preference for honesty and greater transparency of the municipality influence the timeliness of communication. There is evidence that when the GFO and board members have a working relationship built on trust and the GFO has a preference for honesty, the GFO is more willing to share positive information with the board. In addition, there is evidence that with greater transparency and trust in the board, there is a reduction in the time of sharing positive information in situations where there is little discretion in disclosing and less willingness to share information. Research limitations/implications: A principal limitation of this study is the small sample size. In addition, the study was conducted using only participants from the pool of members of the Government Finance Officers Association of Texas. As an exploratory study, the survey included a minimal number of questions to gather data from actual GFOs and included only six possible scenarios. The time constraint resulted in a reduced number of questions related to the models used. Other limitations include the potential of missing variables, factors or perceptions related to scenarios not presented in the survey instrument. Practical implications: The findings suggest that with greater transparency, there is less time between the event and the GFO communication to the board providing the opportunity to improve the effectiveness of the decision-making process. Originality/value: This study is the first to explore the effects of increased transparency on the level of communication between the GFO and the board.